2005
DOI: 10.1124/dmd.105.004390
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sandwich-Cultured Rat Hepatocytes to Determine the Intrinsic Clearance of Compounds With Different Extraction Ratios: 7-Ethoxycoumarin and Warfarin

Abstract: ABSTRACT:The application of sandwich-cultured rat hepatocytes for the identification of the hepatic intrinsic clearance of compounds with widely varying extraction ratios was investigated. We previously showed the applicability of this in vitro system, in combination with a model describing molecular diffusion, hepatocyte/medium partition, and nonsaturated metabolism, which resulted in a successful identification of this parameter for tolbutamide. This approach is further validated using the compounds 7-ethoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…The hepatocyte volume was estimated from cell diameters measured before plating (23 mm). This value is in good agreement with previously published data, which are 16.2 mm for human hepatocytes (Mateus et al, 2013) and 24 mm for rat hepatocytes (Treijtel et al, 2005). The unbound fraction in the hepatocyte homogenate (f u,homogenate ) was calculated using Eq.…”
Section: Transport Experimentssupporting
confidence: 81%
“…The hepatocyte volume was estimated from cell diameters measured before plating (23 mm). This value is in good agreement with previously published data, which are 16.2 mm for human hepatocytes (Mateus et al, 2013) and 24 mm for rat hepatocytes (Treijtel et al, 2005). The unbound fraction in the hepatocyte homogenate (f u,homogenate ) was calculated using Eq.…”
Section: Transport Experimentssupporting
confidence: 81%
“…Other researchers have compared individual metabolic enzyme activity between the two methods independently (Kern et al, 1997;Slaus et al, 2001;Lau et al, 2002;Treijtel et al, 2004). SCH is beneficial for the determination of the metabolic intrinsic clearance of slowly metabolizing compounds, because it allows long-term incubation (Treijtel et al, 2004;Treijtel et al, 2005). The incubation period was up to 24 hours in the present study, whereas Treijtel et al conducted Metabolite profiles of radioactivity were analyzed by radio-HPLC after the incubation of [ metabolic stability studies over 48 hours with SCH for tolbutamide and warfarin and concluded that successful prediction of metabolic intrinsic clearance of these slowly metabolizing drugs was possible.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of differentiated functions, e.g., the decline in cytochrome P-450-dependent biotransformation in hepatocyte cultures (Wortelboer et al, 1991), still is an obstacle in the full use of in vitro systems. The development of more sophisticated culture systems, including cells in an improved matrix environment such as hepatocyte sandwich cultures (Treijtel et al, 2005) or tissue slices (Van de Bovenkamp et al, 2007), shows promising results. Another issue is the fact that metabolism may take place in tissues other than the ultimate target for the toxicity of the metabolite, thus making the determination of the parent compound's toxicity in vitro systems solely consisting of the target tissue for the metabolite of little use.…”
Section: In Vitro-derived Parameters For Biokinetic Modelingmentioning
confidence: 99%
“…Here too, kinetic modeling is a useful tool for the interpretation of the data. An example of such an in vitro biokinetic modeling is the study by Treijtel et al (2005).…”
Section: In Vitro-derived Parameters For Biokinetic Modelingmentioning
confidence: 99%